Pacemaker endocarditis: approach for lead extraction in endocarditis with large vegetations - Vaccarino,Guillermo Nuncio (2009)
The presence of large lead vegetations poses additional difficulties for explantation because many methods cannot be used due to the potential hazard of embolism. We report two patients with large vegetation on the ventricular lead due to endocarditis and one of them with an atrial septal defect associated. It was applied a combined technique of transvenous lead removal and sternotomy with cardiopulmonary bypass for the complete removal of pacemaker wires. This procedure resolved the pacemakers endocarditis safely and subsequently a new transvenous device was placed on the opposite site.